BEYOND THE GUT: EXPLORING NEUROLOGICAL IMPLICATIONS OF CELIAC DISEASE - Karol Sikora; Monika Rogowska; Karolina Wojdat-Krupa; Weronika Ossowska; Maksymilian Czarnota; Klaudia Płudowska; Aleksandra Przelaskowska; Paulina Lewaśkiewicz; Jan Puliński (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: The aim of this article is to provide a comprehensive review of the neurological manifestations associated with celiac disease (CD), a systemic autoimmune disorder triggered by gluten in genetically predisposed individuals. Although CD is traditionally associated with gastrointestinal symptoms, its neurological effects are increasingly recognized and require further analysis.Material and methods: This narrative review was conducted using literature sourced from scientific databases including PubMed, Scopus, Web of Science, and Google Scholar.State of knowledge: Neurological symptoms in CD, such as cerebellar ataxia, peripheral neuropathy, cognitive impairment, seizures, and”brain fog, ” may precede or occur without gastrointestinal symptoms. Diagnostic strategies include genetic and serological testing, neuroimaging, and neurological assessments. Although a gluten-free diet remains the cornerstone of therapy, additional treatments such as vitamin E supplementation and intravenous immunoglobulin have shown promise in specific cases.Results: Neurological symptoms affect a significant proportion of patients with celiac disease, and early diagnosis combined with strict adherence to a gluten-free diet improves treatment outcomes. Quality of life and mental well-being also improve, which is particularly noticeable in the first year of treatment. Celiac disease is characterized by a diverse spectrum of neurological symptoms that may remain undiagnosed without a multidisciplinary approach.